Kemandirian Ekonomi Pesantren Melalui PT Ngabar Mandiri Sejahtera (Studi pada Pondok Pesantren Wali Songo Ngabar) - Muhamad Ulfi; Luhur Prasetiyo (Journal of Economics, Law, and Humanities, 2022)
Independence can be interpreted as the potential to be able to produce to meet their own needs and help others who do not depend on others in carrying out or carrying out a business process. Likewise, in the management of an institution. Economic independence in Islamic educational institutions means that these institutions can choose and carry out activities to survive in a better way. This qualitative descriptive study aims to identify and analyze the economic activities and innovations carried out by PT Ngabar Mandiri Sejahtera and their impact on finansial independence at the Wali Songo Islamic Boarding School, Ngabar. Primary data were obtained from interviews and in-depth observations of and documentation of business unit managers and administrators of the Waqf Maintenance and Development Foundation of the Wali Songo Islamic Boarding School, Ngabar. Secondary data was obtained from the documentation and financial records of PT Ngabar Mandiri Sejahtera. The results show that PT Ngabar Mandiri Sejahtera has various kinds of business units to support the independence of the Wali Songo Islamic Boarding School through its business units, including NBC Supermarkets, Ngabar Food Courts, Ngabar Hostel and Meeting Hall, Ngabar Mart, Ngabar Bistro, Cafeteria Al Azhar, Ngabar Perfume, and Ngabar Laundry. The innovations carried out included developing the type of business, using smart card payment methods cashless, and establishing relationships with third parties to supply the needs of Islamic boarding schools. The impact of economic activities through PT Ngabar Mandiri Sejahtera for the internal boarding school is well-organized sales management, asset improvement, and operating profit. The external is to open up job opportunities for the community around the Wali Songo Islamic Boarding School, Ngabar.